2009
DOI: 10.1109/jqe.2008.2002671
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Electroluminescence on the Spacer Layer Growth Temperature of Multilayer Quantum-Dot Laser Structures

Abstract: Abstract-Electroluminescence (EL) measurements have been performed on a set of In(Ga)As-GaAs quantum-dot (QD) structures with varying spacer layer growth temperature. At room temperature and low injection current, a superlinear dependence of the integrated EL intensity (IEL) on the injection current is observed. This superlinearity decreases as the spacer layer growth temperature increases and is attributed to a reduction in the amount of nonradiative recombination. Temperature-dependent IEL measurements show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…They corresponds to the condition where the dominant carrier recombination mechanism is, radiative ͑m ϳ 1͒, a mixture of radiative and monomolecular nonradiative ͑associated with defects͒ ͑1 Ͻ m Ͻ 2͒, or monomolecular nonradiative ͑m ϳ 2͒. 21 At 10 K, m = 1 was observed at all P e , indicating that radiative recombination is dominant over the entire excitation range investigated. At 77 K, all P e above 2 mW cm −2 had m = 1, but low P e 's data showed m = 1.7.…”
Section: -2mentioning
confidence: 94%
See 1 more Smart Citation
“…They corresponds to the condition where the dominant carrier recombination mechanism is, radiative ͑m ϳ 1͒, a mixture of radiative and monomolecular nonradiative ͑associated with defects͒ ͑1 Ͻ m Ͻ 2͒, or monomolecular nonradiative ͑m ϳ 2͒. 21 At 10 K, m = 1 was observed at all P e , indicating that radiative recombination is dominant over the entire excitation range investigated. At 77 K, all P e above 2 mW cm −2 had m = 1, but low P e 's data showed m = 1.7.…”
Section: -2mentioning
confidence: 94%
“…21 Since dominance of nonradiative recombination is closely related to defect density in the bismide layer, such analysis will also be valuable in comparative PL study of future bismide samples. Using our data for the GaAs 0.97 Bi 0.03 sample, IPL versus P e data are shown as a log-log plot in Fig.…”
Section: -2mentioning
confidence: 99%
“…The gradient, m, indicates the dominant carrier recombination mechanism where m = 1 corresponds to radiative recombination being dominant, or m = 2 where non-radiative monomolecular recombination dominates. Values of 1 < m < 2 indicates a mixture of radiative and non-radiative monomolecular recombination [11]. The analysis shows that the PL emissions for low Bi content samples (LR and LS) are dominated by non-radiative recombination (m = 2) but at higher Bi contents, radiative recombination becomes more significant (m = 1.6 and 1.4 for LV and LT respectively).…”
Section: Photoluminescence Of Gaas 1-x Bi Xmentioning
confidence: 96%
“…Analyzing the dependence of integrated PL (IPL) as a function of excitation power density can provide information of the dominant carrier recombination mechanism (Hasbullah et al 2009). In Figure 5, the integrated PL across the spectral region (~ 0.7-1.55 eV) is plotted on a log-log scale.…”
Section: Power Dependence Of Plmentioning
confidence: 99%
“…Based on their gradients, m, the data in Figure 5 can be categorized into three groups, namely, m ~ 1, 1 <m< 2, and m ~ 2. In this groups, they correspond to the condition where dominant carrier recombination mechanism is radiative (m ~ 1), mixture of radiative and nonradiative (associate with defects) (1 <m< 2), or nonradiative dominant (m ~ 2) (Hasbullah et al 2009). In other study, Martini et al (2011) reported that, in a double logarithmic scale, the integrated PL intensity increases linearly with the increasing excitation power density and can be described by the relation, 2where is the integrated PL intensity; and is the excitation power density (Jin et al 1997).…”
Section: Power Dependence Of Plmentioning
confidence: 99%